2011
DOI: 10.1016/j.anai.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Variations in expression of matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 in nasal mucosa of aspirin-sensitive versus aspirin-tolerant patients with nasal polyposis

Abstract: Background Matrix metalloproteinases (MMPs) are key enzymes responsible for extracellular matrix degradation contributing to the progressive histological changes seen in lower airway disease, including asthma. MMP-9 and TIMP-1 have also shown some role in the pathogenesis of chronic rhinosinusitis (CRS) and nasal polyposis (NP). Objective We aim to determine variability in expression of MMP-9 and its inhibitor, tissue inhibitor of metalloproteinase-1 (TIMP-1), in sinus tissue from distinct patient population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We revealed that fibroblasts and the nasal epithelium are both sources of MMPs within nasal polyps. TIMP‐1 might be able to reduce the effects of the expression of MMP‐9; however, the levels of MMP‐9 and TIMP‐1 were negatively correlated with disease severity in CRS 39,40 . Although higher levels of TIMP‐1 and TIMP‐2 were found in CRSwNPs, we failed to verify the regulatory roles of periostin and tenascin C on TIMPs.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We revealed that fibroblasts and the nasal epithelium are both sources of MMPs within nasal polyps. TIMP‐1 might be able to reduce the effects of the expression of MMP‐9; however, the levels of MMP‐9 and TIMP‐1 were negatively correlated with disease severity in CRS 39,40 . Although higher levels of TIMP‐1 and TIMP‐2 were found in CRSwNPs, we failed to verify the regulatory roles of periostin and tenascin C on TIMPs.…”
Section: Discussionmentioning
confidence: 76%
“…TIMP‐1 might be able to reduce the effects of the expression of MMP‐9; however, the levels of MMP‐9 and TIMP‐1 were negatively correlated with disease severity in CRS. 39 , 40 Although higher levels of TIMP‐1 and TIMP‐2 were found in CRSwNPs, we failed to verify the regulatory roles of periostin and tenascin C on TIMPs. In this regard, further studies are required to illuminate how TIMPs are induced in nasal polyps.…”
Section: Discussionmentioning
confidence: 92%
“…TIMP-1 might be able to reduce the effects of the expression of MMP-9, however, the levels of MMP-9 and TIMP-1 were negatively correlated with disease severity in CRS. [33,34] Although higher levels of TIMP-1 and TIMP-2 were found in CRSwNPs, we failed to verify the regulatory roles of periostin and tenascin C on TIMPs. In this regard, further studies are required to illuminate how TIMPs are induced in nasal polyps.…”
Section: Discussionmentioning
confidence: 92%
“…In previous reports, miR-29b-3p was shown to directly and indirectly regulate MMP-2 and MMP-9 expression ( 28 , 29 ). It is commonly known that MMPs are likely to be associated with airway remodeling in CRSwNPs based on the increased expression of MMP-2 and MMP-9 in patients with CRSwNPs compared with control subjects ( 36 - 38 ). Numerous studies have found that the levels of MMPs are significantly increased in CRSwNPs compared with healthy control tissues and that the levels of TIMPs are significantly decreased ( 10 - 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular mechanisms underlying the development of CRSwNPs remain uncertain, polyp formation occurs due to the protrusion of connective tissue through an initial epithelial defect and remodeling ( 46 ). The present study further demonstrated that MMP-9-integrin β1 complexes promote α-tubulin deacetylation involved in the airway remodeling of CRSwNPs.…”
Section: Discussionmentioning
confidence: 99%